2017
DOI: 10.1016/j.joei.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Ni/SiO2 catalysts prepared at different conditions for hydrogen production from ethanol steam reforming

Abstract: Ni/SiO2 catalysts prepared by a sol-gel method have been investigated for hydrogen production via steam reforming of ethanol using a continuous flow, fixed bed reactor system. Chemical equilibrium calculations were also performed to determine the effects of temperature and molar steam to carbon ratio on hydrogen production. The acidity of the preparation solution (modified by nitric acid and ammonia) and calcination atmosphere (air and N2) were investigated in the preparation of the catalysts. BET surface area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 36 publications
1
20
0
1
Order By: Relevance
“…Two‐stage fixed‐bed reactor has been adopted to perform ethanol reforming test. The reactor setup is shown in Figure , which is similar to our previous work . The ethanol and water mixture with S/C molar ratio of 3 was preheated to 250°C in the first reactor, which was inoculated in first reactor by a syringe pump.…”
Section: Experimental and Methodsmentioning
confidence: 88%
See 2 more Smart Citations
“…Two‐stage fixed‐bed reactor has been adopted to perform ethanol reforming test. The reactor setup is shown in Figure , which is similar to our previous work . The ethanol and water mixture with S/C molar ratio of 3 was preheated to 250°C in the first reactor, which was inoculated in first reactor by a syringe pump.…”
Section: Experimental and Methodsmentioning
confidence: 88%
“…In a study of Kim et al, 30% Ni/SBA‐15 catalyst, S/C ratio of 1.5, and 550°C to 800°C temperature range have been employed for ethanol steam reforming, and the corresponding hydrogen yield could reach about 70% at 700°C. Wu et al obtained a maximum hydrogen yield of 72.0% at 20% Ni/SiO 2 catalyst, S/C ratio of 4, and reforming temperature of 600°C from ethanol steam reforming. These revealed that the performance of the synthesized Ni/CaO catalysts is analogous with other ethanol steam reforming catalysts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that most of the catalyst deactivation of ESR is attributed to the active metal sintering and the deposition of various type of carbon on the surface of the catalyst [41,42]. How to solve these problems is the main challenge in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the nature and composition of the mixed oxides, the different preparation methods of these mixed oxides have been studied to achieve high hydrogen yields , , , , , , . The sol‐gel method can produce a mesoporous structure of the catalysts , , , , , , which can improve the mass transfer efficiency and diminish the deactivation rate . For a zeolite as the support, the sol‐gel incipient wetness impregnation (SIWI) method produces a hierarchical structure, improving the catalyst stability .…”
Section: Effects Of the Supportmentioning
confidence: 99%